Assessing health-related quality-of-life changes in informal caregivers: an evaluation in parents of children with major congenital anomalies - Poley, Marten J. (Springer Netherlands, 2011)
PURPOSE: Relatively few attempts to measure the effects on the health-related quality of life (HRQoL) of informal caregivers within the context of economic evaluations have been reported. This paper is an exploratory attempt to find suitable methods to assess caregivers’ HRQoL, using a population of parents of children with major congenital anomalies. METHODS: A total of 306 parents of children born with either congenital anorectal malformations (ARM) or congenital diaphragmatic hernia were surveyed. They rated their current HRQoL on the EQ-VAS. After that, they rated their HRQoL again on the assumption that someone would take over their caregiving activities completely and free of charge. Finally, the parents classified their HRQoL on the EQ-5D. The caregivers’ scores on the EQ-VAS and the EQ-5D were compared with scores elicited in the general population. RESULTS: Most parents indicated that their HRQoL would not change if someone else took on their caregiving activities. Some methodological issues may have influenced this outcome, such as difficulties in self-assessing HRQoL changes due to caregiving, process utility, protest answers, and difficulties in understanding the hypothetical question. The HRQoL of the parents was relatively low compared with population statistics, especially in the parents of children with ARM and in mothers. This can be illustrated by the difference between the mean EQ-5D score of the mothers aged 25–34 years of the children with ARM and that of the general population (0.83 vs. 0.93; P = 0.002). CONCLUSIONS: Significant HRQoL differences exist between parents caring for children with congenital anomalies and the general population. It would be useful to further improve our understanding of the HRQoL impact of informal caregiving, separating ‘caregiving effects’ from ‘family effects’, and distinguishing parent–child relationships from other caregiving situations. This study underlines the importance of considering caregivers, also in the context of economic evaluations. It indicates that general HRQoL measures, as used in patients, may be able to detect HRQoL effects in caregivers, which facilitates the incorporation in common economic evaluations of HRQoL effects in carers. Analysts and policy makers should be aware that if HRQoL improvement is an important aim, they should register HRQoL changes not only in patients but also in their caregivers.